PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN KELAYAKAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA KONSUMEN KFC DAERAH ISTIMEWA YOGYAKARTA) - Setiawan suju, Etliana Wiliam (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to determine the effect of brand image, product quality and price feasibility on purchasing decisions for KFC consumers. The study used four variables, namely brand image, product quality and price feasibility on purchasing decisions. This research is a qualitative study using questionnaire data obtained from 144 respondents.  The data in this study were processed using IBM SPSS Statistics 24.0. The findings of this study found that brand image has a positive and significant effect on purchasing decisions, price feasibility has a positive and significant effect on purchasing decisions, while product quality has no effect on purchasing decisions and price feasibility has a significant and positive effect on purchasing decisions.